Body Composition of Obese Subjects by Air Displacement Plethysmography: The Influence of Hydration - Le Carvennec, Marie; Fagour, Cédric; Adenis-Lamarre, Emilie; Perlemoine, Caroline; Gin, Henri; Rigalleau, Vincent (Obesity (Silver Spring, Md.), 2007)
OBJECTIVE: We investigated whether air displacement plethysmography (ADP) could detect small changes in body composition of obese subjects with alterations in hydration. RESEARCH METHODS AND PROCEDURES: Ten obese subjects (mean BMI, 39.3 ± 2.8 kg/m²) entered the ADP chamber without and with oil (1, 2, or 4 liters), water (1, 2, or 4 liters), or mixed (1 liter oil + 1 liter water or 2 liters oil + 2 liters water) loads. Real and measured changes in body composition were compared by regression analysis and Bland-Altman procedures. RESULTS: The ADP-measured changes in volume did not differ from the real values and were strongly correlated with them (r = 0.98). In all cases, loads of differing composition and similar volume led to different values of fat, fat-free mass, and percentage fat. Water was detected as increased fat-free mass only with loads of >=2 liters, most of the water being falsely detected as increased fat mass. The observed changes were correlated with the real ones for fat mass (r = 0.68; p < 0.0001), fat-free mass (r = 0.66; p < 0.0001), and percentage fat (r = 0.61; p < 0.0001), but fat mass changes were overestimated by ~1 kg, and fat-free mass changes were underestimated by ~1 kg. This underestimation increased with the highest water loads, as shown by the Bland-Altman plot (r = -0.27; p < 0.05). Percentage fat changes were overestimated by 0.8% (p < 0.001); the magnitude of the error was correlated with the weight of the water load (r = 0.62; p < 0.0001). DISCUSSION: ADP accurately measures changes in body volume, discriminating small changes in body composition. It overestimates changes in adiposity, as most of the increased hydration is detected as an enlarged fat mass.